(−)Epigallocatechin-3-gallate prevents the reserpine-induced impairment of short-term social memory in rats. Issue 8 (December 2015) - Unknown
Abstract : Reserpine has been confirmed to induce cognitive dysfunction and increase brain neural oxidative stress. Green tea catechins, particularly (−)epigallocatechin-3-gallate (EGCG), have strong antioxidative properties and can protect against numerous oxidative damages. In this study, we examined the possible protective effects of EGCG on reserpine-induced impairment of short-term memory in rats. Reserpine (1 mg/kg, intraperitoneal)-induced memory impairment was assessed using the social recognition task method; locomotor activity and the olfactory discrimination ability were not altered as measured by an open-field test and an olfactory discrimination test, respectively. EGCG treatment (100 and 300 mg/kg, intraperitoneal, for 7 days, starting 6 days before the reserpine injection) could improve the worsened social memory of reserpine-treated rats. Also, EGCG treatment reduced reserpine-induced lipid peroxidation and enhanced the antioxidation power in the hippocampi of reserpine-treated rats. These results suggest a protective effect of EGCG in treating reserpine-induced impairment of memory, most probably through its powerful antioxidative activities. Accordingly, EGCG may hold a clinically relevant value in preventing reserpine-induced cognitive dysfunction.